PENGARUH PEMBERIAN MEDIA LEAFLET KOMUNIKASI, INFORMASI, DAN EDUKASI (KIE) TERHADAP TINGKAT PENGETAHUAN PASIEN TENTANG PERAWATAN LUKA PASCA OPERASI ODONTEKTOMI DI RSKGM KOTA BANDUNG - Rustandi, Gista Septiani; Laela, Dewi Sodja; Supriyanto, Irwan (Poltekkes Kemenkes Bandung, 2024)
Prevention of wound infection in patients after odontectomy surgery can be done through proper wound care. Patient knowledge about wound care is one of the important factors that can affect the success of wound care and prevent complications of wound healing after tooth extraction. The purpose of this study was to determine the effect of providing communication, information and education (IEC) leaflet media on the level of patient knowledge about post odontectomy wound care at the Bandung City Dental Hospital. This type of research uses a pre-experimental with a one group pretest-postest approach, which is carried out in a way that before the intervention the variable is observed, the level of knowledge is measured first (prettest) then the intervention is carried out. After the intervention, the measurement is carried out (posttest). Comparison of results between prettest and posttest is assumed to be the result of treatment. The results of this study include the level of patient knowledge about postoperative odontectomy wound care before being given a communication, information and education (IEC) leaflet media including the less category. The level of patient knowledge about postoperative odontectomy wound care after being given communication leaflet media, information and education (IEC) is in the good category. There is an effect of giving communication leaflet media, information and education (IEC) on increasing patient knowledge in post odontectomy wound care.